Exosomes secreted by chemoresistant ovarian cancer cells promote angiogenesis - Zhang Li; Wang Yan-qing; Yang Xiao; Liu Shi-yi; Yuan Meng-qin; Xian Shu; Yang Dong-yong; Zheng Ya-jing; Cheng Yan-xiang (BMC, 2021)
Abstract Background Ovarian cancer (OC) has the highest mortality rate in gynecologic tumors. Despite decades of continuous efforts, the survival rate of patients has not improved significantly, mostly due to drug resistance. Exosomes are hot topics in recent years. Cells can affect the biological behaviors of other cells by transferring exosomes. So far, numerous researchers have found that tumor cells can secrete exosomes which play a important role in the development of tumors. Solid tumors can promote angiogenesis. When drug resistance occurs, it seems that more blood vessels form. We suppose that exosomes derived from chemoresistant OC cells can also promote angiogenesis. Results We investigate whether exosomes secreted by chemoresistant SKOV3-DDP cells (SKOV3-DDP-exo) and sensitive SKOV3 cells (SKOV3-exo) influence angiogenesis. After exosomes were extracted, exosomes were co-cultured with HUVECs. We found that SKOV3-DDP-exo and SKOV3-exo are absorbed by endothelial cells and promote the proliferation, migration, invasion and tube formation of endothelial cells. Moreover, SKOV3-DDP-exo is more powerful in angiogenesis, suggesting that parts of the components of SKOV3-DDP-exo are significantly radical. We also found that miR-130a was highly expressed in drug-resistant OC cells. Also, we found that miR-130a in SKOV3-DDP-exo is higher than SKOV3-exo. Therefore, we suggest that miR-130a in exosomes is the main cause of chemoresistant OC cells promoting angiogenesis.